Characteristics of torsional ground motions obtained for Turkey and their appraisal against Eurocode 8 - Sisman, Rafet; Taciroglu, Ertugrul (SPRINGER, 2024)
In current engineering practice, the torsional effects of ground motions are only considered implicitly through accidental eccentricity coefficients. In seismic design codes, these coefficients account for not only the unintended (or uncertain) asymmetric distributions of structural mass and stiffness in the plan but also the torsional components of ground motions. The torsional effects may develop due to wave passage effects or the incoherency of translational ground motions along the foundation systems. While it is possible to obtain torsional components of ground motions directly from seismic records with modern instruments, such sensors are uncommon. Therefore, several numerical procedures have been proposed in the literature for estimating torsional components of ground motions from translational measurements. In this study, the Single Station Procedure (SSP)-based on the deconstruction of translational ground motions into body waves and the subsequent reconstruction of rotational ground motions-is employed to obtain torsional ground motions for seven different seismic events in Turkey. Additionally, the corresponding accidental eccentricity coefficients that can cause the same response modification with torsional ground motions are determined. First, a conventional procedure is utilized to obtain the corresponding accidental eccentricity coefficients. Various drawbacks of the conventional procedure, such as negative eccentricity coefficients, are addressed. Then, a relatively obscure definition of accidental eccentricity is revived to propose a novel procedure for determining accidental eccentricity coefficients. It is observed that the proposed procedure yields higher values for the accidental eccentricity coefficients than the conventional procedure. It also observed that the torsional spectrum provided in Eurocode 8 provisions requires higher eccentricity values than those implied by the recorded ground motions from Turkey.
Keywords: Torsional ground motions; Accidental eccentricity; Torsional response spectrum; Response amplification due to torsion; ROTATIONAL COMPONENTS; DENSE-ARRAY; EARTHQUAKE; Engineering; Geology